Kajian Yuridis Pengesahan Perkawinan di Pengadilan Agama - K, Siti Mardhatilla Habiba; Rahman, Muh. Sabir; Syahril, Muh. Akbar Fhad (Jurnal Litigasi Amsir, 2023)
This study aims to determine the judge’s legal considerations for the legalization of marriage (isbat nikah) based on decision no. 189/Pdt.P/2021/PA.Pare, and application of judge’s law to the legalization of marriage (isbat nikah) based on decision no. 189/Pdt.P/2021/PA.Pare. This research uses a type of normative research with a statutory approach and a case study approach, the data collection techniques used are observation, interviews, and documentation. The types and sources of legal materials use primary legal materials, secondary legal materials, and tertiary legal materials. The results of this study indicate that determining the case for a marriage certificate by the judge in decision No. 189/Pdt.P/2021/PA.Pare by the applicants Hriyandi bin H. Abd Rahman and Khofifah Nur Syahrah bint Hasbulla were declared legally valid. The marriage of the applicants is following Islamic law and has fulfilled the provisions of Article 14 to Article 30 of the Compilation of Islamic Law regarding the terms and pillars of marriage.